The Role of Banks in the Transmission of Monetary Policy in the Baltics - Matthias Köhler; Judith Hommel; Matthias Grote (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
The paper empirically investigates the monetary transmission mechanism in the Baltic States. The analysis of the transmission channels through which monetary policy shocks are transmitted is particularly important for the European Central Bank that makes monetary policy in an enlarged European Monetary Union. The paper focuses on the bank lending channel of monetary transmission due to the importance of banks in the financial system of the Baltic countries. The existence of this transmission channel is tested by using a panel structural approach that distinguishes banks according to size, capitalization, liquidity and ownership structure. The results indicate that a bank lending channel is present in the Baltic States and mainly caused by differences in liquidity.
Keywords: E43; G21; E44; G15; 330; Monetary Transmission; Bank Lending Channel; Transition Countries; Transmissionsmechanismus; Kreditkanal; Übergangswirtschaft; EU-Erweiterung; Schätzung; Nordosteuropa